Price Responses to Index Additions and Deletions: A Systematic Review with Bibliometric Analysis - Goyal, Priyanka; Soni, Pooja (Gyan Management Journal, 2023)
The present study aims to systematically review the research evidence available on the impact of additions and deletions of companies from various stock indices on their stock prices and provide directions for future research. This study followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 flow diagram to select the final sample of 44 studies for systematic literature review using the Scopus database. These research studies have been reviewed subsequently to categorize, synthesize and map the extant literature using R studio. The study found that, on average, there is an increase in share prices of stocks being added to an index and stocks being excluded from the index evidenced negative abnormal returns. But the existing literature doesn’t provide conclusive evidence on whether these price effects are long or short-term. The study guides the investors, traders and other market participants regarding their long and short positions in the market and also provides future research directions to academicians.